Multi-platform mediation: U.S. mothers' and fathers' mediation of teens' media use. Issue 4 (2nd October 2017) - Warren, Ron
Abstract: This study attempts to solidify a predictive model of parental mediation across four media platforms (television, video games, internet, and cellphones). The analysis compares U.S. mothers' and fathers' mediation, specifically within the larger context of parenting behaviors and media attitudes. Results indicate that there are only a few, small gender differences in parental mediation. Across media, parental mediation was largely predicted by the child's age, parents' attitudes about media effects, and levels of parent–child involvement and communication. More involved parents were more frequent mediators for television, video games, and the Internet. Parents who reported frequent talks with children more frequently mediated all four media. The results are discussed within the context of research on parenting.